A geomorphometric model to determine topographic parameters controlling wildfires occurrence in tropical dry forests. (March 2022) - Quesada-Román, Adolfo; Vargas-Sanabria, Daniela
Abstract: Tropical dry forests (TDF) are commonly affected by wildfires, especially during the dry season and drought periods. Many studies have identified ecological, pedological, and climatic variables that control fires ignition as well as other anthropogenic causes. Nonetheless, the intrinsic geomorphometric variables that shape the different TDF landscapes have been underestimated. Hence, we used a Generalized Linear Model (GLM) to study the occurrence of wildfires in a TDF on a TDF located in a protected area at northwest Costa Rica. The influences of nine topographic parameters (TP) were tested on the occurrence of wildfires during a period of 23-years (1997–2020). The statistical analysis demonstrate that Aspect (compass direction that a terrain surface faces) and Wind Exposition (areas degree exposed to wind) are the most influential TP to explain the wildfires occurrence in TDF. The results may be valuable for the understanding and assessment of geomorphometric variables controlling wildfires occurrence in TDF. Therefore, highlighting the importance of fire risk management in ecosystems comprising almost the half of the total of tropical forests proves relevant. Highlights: Different topographic parameters influence wildfires in TDF landscapes. A geomorphometric model determined the topographic parameters controlling wildfires in TDF. The most influencing topographic parameters were determined at northwest Costa Rica. Aspect and Wind Exposition were the most influential topographic factors. This model can be applied in other tropical forests.